2006
DOI: 10.3892/or.15.2.425
|View full text |Cite
|
Sign up to set email alerts
|

Mib-1 proliferation index is an independent predictor of lymph node metastasis in invasive breast cancer: A prospective study on 675 patients

Abstract: Abstract. In order to evaluate the potential risk factors for Lymph node metastasis in invasive breast cancer patients submitted to axillary dissection, 675 patients who received surgery between January 1995 and December 2002 were included in a prospective study. In all cases, MIB-1 proliferation index was investigated by immunohistochemistry. Lymph node involvement was found in 248 out of 675 patients. Univariate analysis showed that peritumoral lymphovascular invasion, pT stage, tumor multiplicity, MIB-1 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
1
7
0
2
Order By: Relevance
“…Furthermore, these findings are supported by the results showing that tumours with ‘high’ Ki67 in tumour resections had a significantly higher probability for lymph node metastasis. Similar findings were reported by Marrelli et al ,41 although a lower cut-off for high proliferation (≥10%) was used 41. High proliferation by Ki67 evaluated on whole sections and tissue microarrays has been associated with lymph node metastasis 40.…”
Section: Discussionsupporting
confidence: 64%
“…Furthermore, these findings are supported by the results showing that tumours with ‘high’ Ki67 in tumour resections had a significantly higher probability for lymph node metastasis. Similar findings were reported by Marrelli et al ,41 although a lower cut-off for high proliferation (≥10%) was used 41. High proliferation by Ki67 evaluated on whole sections and tissue microarrays has been associated with lymph node metastasis 40.…”
Section: Discussionsupporting
confidence: 64%
“…Some previous studies revealed that a high Ki-67 expression level was associated with more frequent lymph node metastasis in patients with all types of breast cancer, but they did not investigate an association between p53 expression and nodal metastasis. 7,25,26 Our findings demonstrated that a high expression level of Ki-67 (>10%) but not p53, although both are considered prognostic markers for breast cancer, was significantly associated with axillary nodal metastasis in patients with TN and high-grade non-TN tumors, indicating that Ki-67 has a better prognostic value than p53 for these breast carcinomas. Previous studies have demonstrated that TN breast tumors are more frequently associated with lymph node metastasis compared with non-TN tumors.…”
Section: Discussionmentioning
confidence: 68%
“…MIB1 (mindbomb homologue 1 ( Drosophila )), a monoclonal antibody against the Ki-67 antigen (1:250 dilution), was used to identify proliferating cells within the tumour tissue. The proliferating cell index (PCI) of the tumours was estimated by examining the stained slides using a square graticule at high magnification (×100) as described previously 24 25…”
Section: Methodsmentioning
confidence: 99%